Qawaid Fiqhiyah's Review of Buying Shoes With a Paid Lots System at Toidiholic Store Bandar Lampung - Jayusman Jayusman; Rahmat Hidayat; Rizki Zulu Febriansyah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
In the practice of buying and selling at the Toidiholic Store there is one system, namely a paid lottery. This is done in the sale and purchase of limited edition shoes with a large demand. The focus of this research is how Qawaid Fiqhiyah analyzes the practice of buying and selling shoes with a paid lottery system at the Toidiholic Store Bandar Lampung. This study concludes that this lottery is a lottery that is permitted by Islamic law because it is carried out solely to create a sense of justice and prevent chaos and prevent wholesale buying of shoes if sold normally or without a lottery. Although the cost of the lottery coupon is sold for Rp. 20,000, - but the fee is still within reasonable limits as a registration or administration fee for holding a lottery activity, considering that the benefit element in this lottery is greater than the harmful element.